LEVERAGING CHOCOMEL BRAND ENGAGEMENT BY UNDERSTANDING GEN Z CONSUMER PREFERENCE IN SPAIN: HARNESSING DIGITAL TO CHANGE THE GAME - Mahendra Sarwono, Mutiara Dwi; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to determine the relevant strategy to engage with the target consumer, the Zoomers, by analysing their buying behaviour and purchasing decisions for Chocomel, one of the flavoured dairy drink companies in Spain. Concurrently, the company has no experience in approaching and engaging this target group in Spain. The approach is expected to boost brand recognition, purchase intention, and engagement. In order to establish an effective strategy, comprehensive data is required. Therefore, the authors gather information during their internship and distributed questionnaires to Spanish Gen Z who have previously purchased Chocomel. The findings of this study indicate that Chocomel's new target market in Spain, Generation Z, shows passive (71%) engagement assessed from five conceptual relationships of consumer brand engagement, whereas purchasing intent and customer enthusiasm are high. This indicates that Chocomel has an encouraging opportunity in this market and has to improve brand recognition to promote meaningful engagement. In addition, this study recommends establishing a transparent, perceptible engagement approach and prioritising personalization in order to foster brand recognition and consumer engagement. In the recommendation chapter, the author additionally specifies the strategies Chocomel must comply with to optimise the entire consumer journey, enabling the company to acquire long-term relationships with customer